ARAB COUNTRIES AND THE DOHA ROUND: BETWEEN CONTRADICTIONS AND BALANCES - Kazzi, Habib (European Scientific Journal, ESJ, 2014)
Since 2001, the World Trade Organization (WTO) has launched the Doha Round that aims to speed up the liberalization of trade policies while ensuring for developing countries, in particular the least developed among them, a share in the growth of world trade that corresponds to the needs of their economic development. However, like many developing countries, the Arab countries have ambiguous relationships with the multilateral negotiations process, ambiguity that characterizes more generally their position within theWTO. The Doha Round has shown the Arab countries’ adherence to the virtues of free trade and their desire of deeper integration in the multilateral trading system. At the same time, the impact of the Arab countries on the conduct of the negotiation process remains low and reflects, ultimately, their marginalization in the WTO system. This contribution endeavors to analyze the key issues of the Doha Round for Arab countries and the reasons of this ambiguity.